Proceedings of the 1st ACM SIGMOBILE International Workshop on Systems and Networking Support for Healthcare and Assisted Livin 2007
DOI: 10.1145/1248054.1248061
|View full text |Cite
|
Sign up to set email alerts
|

Investigating network architectures for body sensor networks

Abstract: The choice of network architecture for body sensor networks is an important one because it significantly affects overall system design and performance. Current approaches use propagation models or specific medium access control protocols to study architectural choices. The issue with the first approach is that the models do not capture the effects of interference and fading. Further, the question of architecture can be raised without imposing a specific MAC protocol. In this paper, we first evaluate the star a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 8 publications
1
61
0
Order By: Relevance
“…The work presented in [47] was the first attempt to point the benefits of using multi-hop communications in wireless body area networks (WBAN). Later, Natarajan et al experimentally investigated the impact of network topology on the average number of retransmissions, network lifetime [48] and packet delivery ratio [49]. They concluded that the multi-hop strategy is more reliable especially in outdoor settings.…”
Section: Routingmentioning
confidence: 99%
See 1 more Smart Citation
“…The work presented in [47] was the first attempt to point the benefits of using multi-hop communications in wireless body area networks (WBAN). Later, Natarajan et al experimentally investigated the impact of network topology on the average number of retransmissions, network lifetime [48] and packet delivery ratio [49]. They concluded that the multi-hop strategy is more reliable especially in outdoor settings.…”
Section: Routingmentioning
confidence: 99%
“…Indeed, all existing WSN for rehabilitation adopted a star topology with one-hop communications between each node and the gateway. However, there are evidence that multi-hop communications can be better than one hop communications in several cases [48] [49]. Thus, multi-hop communications should be used in rehabilitation applications and their performance should be investigated.…”
Section: Routingmentioning
confidence: 99%
“…Yun et al [11] studies the energy-efficient communications for BodyNets. NUS group studies the architecture of BodyNets and proposes their own architecture [12]. More research works have also been conducted on the BodyNet adaptability, self-organization, middle-ware, signal processing, system reliability and healthcare and monitoring [12][13][14][15].…”
Section: Background and Related Workmentioning
confidence: 99%
“…NUS group studies the architecture of BodyNets and proposes their own architecture [12]. More research works have also been conducted on the BodyNet adaptability, self-organization, middle-ware, signal processing, system reliability and healthcare and monitoring [12][13][14][15]. There are also some promising BodyNet research projects such as CodeBlue [16], MobiHealth [17], MIThril [18] and MyHeart [13].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Natarajan et al [5] highlighted the existence of the inter-user interference, and found that such interference reduces packet delivery rate by Copyright(c) 2015 IEEE. Personal use of this material is permitted.…”
Section: Introductionmentioning
confidence: 99%